Conference Record of the Twenty Sixth IEEE Photovoltaic Specialists Conference - 1997
DOI: 10.1109/pvsc.1997.654162
|View full text |Cite
|
Sign up to set email alerts
|

Triple-junction amorphous silicon alloy PV manufacturing plant of 5 MW annual capacity

Abstract: A spectral-splitting, triple-junction a-Si alloy solar cell processor has been designed, built and optimized. A rollto-roll process has been used to deposit two layers of back reflector, a triple-cell structure with nine layers of a-Si and a-SiGe alloys and a single layer of antireflection coating consecutively on a half-a-mile roll of stainless steel. The coated web is next slabbed and processed to make a variety of products. The design of the machine and processes used incorporate several key features develo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…A field study in Arizona US showed that an a-Si module had 30% more battery charging capacity (amp-hrs) compared to a c-Si module of the same STC power rating. 68 Another reason for the higher energy rating is the thermal annealing of light-induced defects which gives a-Si has its seasonal high efficiency in the summer when the warm days and nights help to anneal light-induced defects, and the solar irradiance is highest. Interestingly, the temperature coefficient for single, double or triple junction a-Si modules is approximately the same.…”
Section: Higher Annual Energy Productionmentioning
confidence: 99%
“…A field study in Arizona US showed that an a-Si module had 30% more battery charging capacity (amp-hrs) compared to a c-Si module of the same STC power rating. 68 Another reason for the higher energy rating is the thermal annealing of light-induced defects which gives a-Si has its seasonal high efficiency in the summer when the warm days and nights help to anneal light-induced defects, and the solar irradiance is highest. Interestingly, the temperature coefficient for single, double or triple junction a-Si modules is approximately the same.…”
Section: Higher Annual Energy Productionmentioning
confidence: 99%
“…Of the thin film cell options, the CuInS2 cells provides superior projected performance and no Staebler-Wronski losses which allows for the smallest feasible PV array size. However, the CuInSz cell design and manufacturing maturity is lower than the competing a-SiGe cell technology that has a strong terrestrial manufacturing base [26].…”
Section: Bccause Of the Relatively Small Eps Mass Andmentioning
confidence: 99%